To bind or not to bind: Cistromic reprogramming in prostate cancer - Shen, Michelle; Demers, Léa-Kristine; Bailey, Swneke D.; Labbé, David P. (Frontiers in Oncology, 2022)
The term “cistrome” refers to the genome-wide location of regulatory elements associated with transcription factor binding-sites. The cistrome of key regulatory factors in prostate cancer etiology are substantially reprogrammed and altered during prostatic transformation and disease progression. For instance, the cistrome of the androgen receptor (AR), a ligand-inducible transcription factor central in normal prostate epithelium, is directly impacted and substantially reprogrammed during malignant transformation. Accumulating evidence demonstrates that additional transcription factors that are frequently mutated, or aberrantly expressed in prostate cancer, such as the Forkhead Box A1 (FOXA1), the ETS-related gene (ERG), and the MYC proto-oncogene, contribute to the reprograming of the AR cistrome. In addition, recent findings have highlighted key roles for the SWI/SNF complex and the chromatin-modifying helicase CHD1 in remodeling the epigenome and altering the AR cistrome during disease progression. In this review, we will cover the role of cistromic reprograming in prostate cancer initiation and progression. Specifically, we will discuss the impact of key prostate cancer regulators, as well as the role of epigenetic and chromatin regulators in relation to the AR cistrome and the transformation of normal prostate epithelium. Given the importance of chromatin-transcription factor dynamics in normal cellular differentiation and cancer, an in-depth assessment of the factors involved in producing these altered cistromes is of great relevance and provides insight into new therapeutic strategies for prostate cancer.